A Comparison of US Federal Government Spending for Research and Development Related to Public Health Preparedness Capabilities, 2008–2017. (22nd August 2020) - Keim, Mark; Kirsch, Thomas D.; Lovallo, Alex
ABSTRACT: Objective: The Centers for Disease Control and Prevention developed 15 National Public Health Emergency and Preparedness Response Capabilities (NPHPRCs) to serve as national standards for health-related core capabilities. The objective of this study is to determine the level of federal funding allocated for research related to NPHPRCs during 2008–2017. Methods: An online search of http://www.USAspending.gov was performed to identify federal awards, grants, contracts from 2008–2017 related to research associated with NPHPRCs. Inclusion criteria were identifiable as research and disaster-related; US-based; and specific reference to any of the NPHPRCs. A panel of 3 experts reviewed each entry for inclusion. Results: The search identified 15 278 transactions representing US $29.2 billion in awards. After exclusions, 93 entries were found to be related to NPHPRCs, averaging US $2 783 136 annually. Funding notably dropped to US $168 684 in 2010 and ceased entirely in 2016. Ten (67%) of NPHPRCs received funding. Eighty-percent of funding focused on 4 capabilities. Three federal agencies funded 80% of research. Sixteen (24%) of the 47 recipients received 80% of all funding. Conclusion: US federal investments in research and development related to NPHPRCs have been highly variable over the past decade. One-third of NPHPRCs receive no funding. There are notable gaps in funding, content, continuity, and scope of participation.